2009
DOI: 10.1093/europace/eup309
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular systolic dysfunction by itself does not influence outcome of atrial fibrillation ablation

Abstract: AimsThe objective of the study was to analyse the influence of left ventricular (LV) ejection fraction (EF) on the outcomes of atrial fibrillation (AF) ablation after a first procedure. Pre-procedural predictors of recurrences after AF ablation can be useful for patient information and selection of candidates. The independent influence of LV systolic dysfunction on recurrence rate has not been studied.Methods and resultsA case–control study (1:1) was conducted with a total of 72 patients: 36 cases (depressed L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 27 publications
0
22
2
Order By: Relevance
“…Several studies reported on improvement in LV systolic function, quality of life, exercise tolerance and functional class, mitral regurgitation, reduction of heart failure hospitalizations and incidence of stroke. [16][17][18][19][22][23][24][25][26][27][28][31][32][33] Two studies selectively focused on patients with TCM, specifically 113 individuals. AF ablation efficacy at followup (six to 18 months) was 74%, and mean LVEF significantly improved from 35% or 40% to 54%, suggesting that TCM did not increase the risk of AF recurrence.…”
Section: Search Resultsmentioning
confidence: 99%
“…Several studies reported on improvement in LV systolic function, quality of life, exercise tolerance and functional class, mitral regurgitation, reduction of heart failure hospitalizations and incidence of stroke. [16][17][18][19][22][23][24][25][26][27][28][31][32][33] Two studies selectively focused on patients with TCM, specifically 113 individuals. AF ablation efficacy at followup (six to 18 months) was 74%, and mean LVEF significantly improved from 35% or 40% to 54%, suggesting that TCM did not increase the risk of AF recurrence.…”
Section: Search Resultsmentioning
confidence: 99%
“…16 A third case controlled series reported that the efficacy of AF ablation was similar in patients with an without LV systolic dysfunction and also reported an improvement in EF at six months follow-up. 17 A recent meta-analysis reported that the single procedure efficacy of AF ablation was lower in patients with systolic dysfunction, but with repeat procedures a similar success rate could be achieved among patients with and without systolic dysfunction. 50 Overall, catheter ablation of AF is a reasonable in highly selected patients with heart failure.…”
Section: Areas Of Uncertainty and New Techniquesmentioning
confidence: 99%
“…1,5 Yet published data also supports a role for catheter ablation in patients who were previously deemed unsuitable. Benefit from ablation has been reported in patients with heart failure [14][15][16][17] …”
Section: Rationale For Catheter Ablation Of Afmentioning
confidence: 99%
See 1 more Smart Citation
“…A third case-control series reported that the efficacy of AF ablation was similar in patients with and without left ventricular systolic dysfunction and also reported an improvement in ejection fraction at 6-month follow-up. 41 A recent meta-analysis 42 reported that the single-procedure efficacy of AF ablation was lower in patients with systolic dysfunction, but with repeat procedures, a similar success rate could be achieved among patients with and without systolic dysfunction. Taken as a whole, the results of these studies suggest that catheter ablation of AF is reasonable in highly selected patients with heart failure.…”
Section: Some Unanswered Questions Concerning the Outcomes Of Af Ablamentioning
confidence: 99%